THU0438 Is Skin Disease More Important to Patients or Physicians in the Assessment of Disease Activity in Psoriatic Arthritis?. (10th June 2014) - Sholter, D.; Rahman, P.; Avina-Zubieta, J.A.; Kelsall, J.; Arendse, R.; Khraishi, M.; Shaikh, S.; Bensen, W.G.; Rampakakis, E.; Sampalis, J.S.; Nantel, F.; Shawi, M.; et al.
Abstract : Background: Patient (PtGA) and physician (MDGA) global assessment of disease activity are standard outcome measures used in clinical practice and research to ascertain patient and physician subjective perception of disease activity in psoriatic arthritis (PsA). Given that the PtGA and MDGA measure the same construct from two different perspectives, assessing their concordance may provide valuable insight on patient and physician differences with respect to the relative importance placed on specific disease parameters. Objectives: The aim of this analysis was to assess the agreement between PtGA and MDGA, and to compare the correlation of PtGA or MDGA with the Psoriasis Area and Severity Index (PASI) in PsA patients treated with infliximab (IFX) in a Canadian real-world, routine clinical practice setting. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for rheumatoid arthritis, ankylosing spondylitis, or PsA with IFX or golimumab as first biologics or after having been treated with a biologic for <6 months. Eligible people for this analysis included PsA patients treated with IFX who were enrolled between 2005 and 2012. The correlation between disease parameters was assessed with the Spearman's rho coefficient (r), while the intraclass correlation coefficient (ICC) and Cronbach's alpha (CA) was used to assess internal consistency. Results: A total of 92 patients (52.2% male) were included with a mean (SD) age of 48.7 (9.9) years and disease duration of 6.8 (9.1) years. At baseline, mean (SD) disease parameters were: PASI =3.3 (5.6); swollen joint count (SJC28) =4.0 (3.8); tender joint count (TJC28) =5.9 (5.3); PtGA =5.0 (2.8); MDGA =5.8 (2.2) cm. Prior to IFX initiation, 78 (84.8%) patients had been treated with a traditional DMARD (71.7% with methotrexate). Overall, a strong agreement was observed between PtGA and MDGA (r=0.632). The correlation of PASI with PtGA was low (r=0.213), whereas it was moderate with MDGA (r=0.343) (Figure 1 ). Overall, internal consistency was poor between PASI and both PtGA (CA =0.373, ICC =0.229) and MDGA (CA =0.445, ICC =0.286) although it was higher with the latter. Multivariate linear regression resulted in the exclusion of PtGA from the model, also supporting the stronger association of MDGA with PASI. When considering other disease parameters, PtGA showed a very strong correlation with pain (r=0.885) and strong with HAQ-DI (r=0.596), whereas a strong correlation was observed between MDGA and both pain and HAQ-DI (r=0.652 and r=0.520, respectively). Conclusions: The results of this analysis shows that the association of PASI is stronger with MDGA when compared to PtGA. However, patient-reported pain and HAQ-DI were better correlated with PtGA and MDGA when compared to PASI, suggesting that both patients and rheumatologists place more emphasis on pain and functional activity than on skin symptoms when evaluating the global status of PsA. Disclosure of Interest: : D. Sholter: None declared, P. Rahman: None declared, J. A. Avina-Zubieta: None declared, J. Kelsall: None declared, R. Arendse: None declared, M. Khraishi: None declared, S. Shaikh: None declared, W. Bensen: None declared, E. Rampakakis: None declared, J. Sampalis: None declared, F. Nantel Employee of: Janssen Inc Canada, M. Shawi Employee of: Janssen Inc Canada, S. Otawa Employee of: Janssen Inc Canada, A. Lehman Employee of: Janssen Inc Canada DOI: 10.1136/annrheumdis-2014-eular.5316